2019
DOI: 10.1080/16070658.2019.1607481
|View full text |Cite
|
Sign up to set email alerts
|

A review of adolescent nutrition in South Africa: transforming adolescent lives through nutrition initiative

Abstract: In South Africa, urbanisation is associated with substantial burdens of adolescent overweight and obesity, making teenagers vulnerable to longer-term non-communicable diseases. In addition, as potential future parents, the nutritional status of adolescents is increasingly recognised as a key driver of health and well-being in the next generation. This review reported on the available literature examining nutritional status and dietary intakes and practices, as well as their determinants, in South African adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 108 publications
(478 reference statements)
2
21
1
1
Order By: Relevance
“…Social support, whether from peers or family members, can have both positive or adverse effects on dietary behaviours and eventual onset of overweight/obesity. Family members and sharing meals with the larger family was associated with better eating habits in early adolescence, but not in older ages [26,47]. Particularly, the presence of grandparents at home might contribute to a healthier weight status among mobile/migrated families but not in societies with little geographic mobility [22].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Social support, whether from peers or family members, can have both positive or adverse effects on dietary behaviours and eventual onset of overweight/obesity. Family members and sharing meals with the larger family was associated with better eating habits in early adolescence, but not in older ages [26,47]. Particularly, the presence of grandparents at home might contribute to a healthier weight status among mobile/migrated families but not in societies with little geographic mobility [22].…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative research or mixed methods papers provided deeper insights into determinants of food choices [25,26,29,34,35,42], while quantitative papers provided more measurable effect sizes [24,40,41,44] useful, e.g., for future sample size calculations. Systematic reviews are not yet a cross-disciplinary accepted methodology as the authors of the reviews come mainly from health/nutrition and life science arenas [22,26,30,32,33,39,40,41]. It is underscored that some of the reviews are by authors from business economics [38], food science [36], sensory science [31] and marketing [29], highlighting the potential for cross-disciplinary collaboration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the South African Health and Nutrition Examination Study (SANHANES) of 2012 [5], the combined prevalence of overweight and obesity was 26.8% in 15 to 17-year-old females and 48.8% in 18 to 24 year-old females, implying an even greater increase. A recent review of cross-sectional studies undertaken on South African adolescents in urban and rural settings showed an overall increase in the combined prevalence of overweight and obesity with age in adolescents from age 10 to 20-years, mostly because of an increase in obesity in females [6]. Briefel and Johnson (2004), evaluating secular trends in dietary intake in the United States over 30 years, found that in children 1 to 19-years-old energy intake had increased little except in adolescent females [7].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents experience more time away from the family than younger children and hence are exposed to many foods which may not be the norm at home. Growing levels of independence make adolescents more susceptible to the development of obesogenic behaviors which increases the risk of obesity [6]. Numerous studies have examined sedentary behaviors in adolescents, especially television (TV) watching and/or excessive screen time, and found them to be associated with a less healthful diet [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%